Effect of polyphenol concentrations on astringency perception and its correlation with gelatin index of red wine - Goldner, María Cristina (2010)
Fil: Goldner, María Cristina. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina